(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The current study aimed to clarify the internal requirements that enable Prince Sattam bin Abdulaziz University (PSAU) to enter the Fourth Industrial Revolution (IR4) to discover the variables that help PSAU to achieve global positions. The study used the descriptive method, and the designed questionnaire consisted of 39 items, it was divided in two dimensions that was applied to a sample of the faculty members (100 members), the study presented the faculty members’ vision for the university education future in light of IR4 in general; The internal requirements dimension enables PSAU to enter IR4 has the highest average 3.74, followed by the dimension that enables PSAU to achieve advanced positions internationally in light of IR4 and it has an average of 3.46. The results also showed that there were no statistically significant differences due to the impact of the scientific rank, and according to the specialization variable while differences were found due to the gender and years of experience variables. Also, the study presented a proposal launching strategy for the education future at PSAU in light of IR4 to activate PSAU’s role to enter IR4 world.